O-008 High-frequency optical coherence tomography for imaging neurovascular implants in tortuosity. (22nd July 2019) - Puri, A; Marosfoi, M; Ughi, G; King, R; Langan, E; Chueh, J; Gounis, M
Abstract : Introduction: Intravascular optical coherence tomography (OCT) has an established role in the diagnosis and image guided treatment of coronary artery disease. However, due to the profile and design of the catheter, these devices are not suitable for routine application in neurointerventional surgery. We aim to demonstrate that new generation high frequency OCT (HF-OCT) can image stents and flow diverters used to treat intracranial aneurysms with acceptable workflow deployed in neurointerventional surgery. Materials and methods: An HF-OCT prototype was built (Gentuity, Sudbury MA) that is compatible with standard microcatheters (0.017'). An in vitro flow loop consisting of a patient-specific vascular replica and using porcine blood as a working fluid was deployed to test contrast infusion protocols necessary to remove blood from the target vascular section. Subsequently, eight pigs were implanted bilaterally with flow diverters and stents. The presence of acute platelet aggregation on the surface of the devices and malapposition of the device to the vessel wall was assessed by 3 raters reviewing digital subtraction angiography (DSA), high resolution cone beam CT (CBCT), and HF-OCT. Finally, using the tortuous porcine brachial artery, HF-OCT was performed, and image quality assessed. Results: In the in vitro experiment, the optimized contrast infusion protocol was delivery of contrast through the intermediate catheter (0.058' Navien, Medtronic Neurovascular, Irvine CA) delivering the HF-OCT device at a rate of 5 ml/s for 20–25 ml of contrast. This protocol resulted in complete clearing of highly attenuating erythrocytes for an optically clear field. In the pig study, the agreement by the reviewers (Fleiss kappa) regarding clot formation at 3 distinct locations along the flow diverter was 0.49, 0.67 and 0.90 for DSA, CBCT and HF-OCT, respectively. The agreement for diagnosing malapposition at these locations was 0.18, 0.67 and 0.87 for DSA, CBCT, and HF-OCT, respectively. In the porcine tortuosity model, in all cases, navigation and imaging was performed with uniform illumination and free from artifact. Conclusion: An HF-OCT device has been built that is compatible with neurointerventional surgery workflow and cerebrovascular anatomy. Preclinical data demonstrate consistent improvement to diagnose acute platelet aggregation and malapposition of flow diverters as compared to existing imaging modalities (figure 1). Disclosures: A. Puri: 1; C; NIH. M. Marosfoi: None. G. Ughi: 4; C; Gentuity. 5; C; Gentuity. R. King: None. E. Langan: None. J. Chueh: None. M. Gounis: 1; C; NIH.